2019
DOI: 10.1177/1071181319631261
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Trunk-Supporting Exoskeleton

Abstract: Trunk Supporting Exoskeletons are increasingly being evaluated in workplaces as viable ergonomic interventions for reducing the risk of back injuries. A series of trunk-supporting exoskeletons have been designed and built at the University of California at Berkeley and suitX. These exoskeletons decrease the forces on the wearer’s back at L5/S1 location. This article describes one of these exoskeletons, referred to as backX, and its evaluation method. backX is designed not only to reduce the forces and torques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 5 publications
1
26
1
Order By: Relevance
“…Varieties of passive exoskeletons have been developed, for instance, PLAD [4][5][6], WMRD [7], BNDR [8], VT/Lower [9], SPEXOR [10], Laevo [11], and BackX [12]. PLAD uses elastic bands to reduce the muscle load of the vertical spine when lifting.…”
Section: Introductionmentioning
confidence: 99%
“…Varieties of passive exoskeletons have been developed, for instance, PLAD [4][5][6], WMRD [7], BNDR [8], VT/Lower [9], SPEXOR [10], Laevo [11], and BackX [12]. PLAD uses elastic bands to reduce the muscle load of the vertical spine when lifting.…”
Section: Introductionmentioning
confidence: 99%
“…It showed a significant improvement in the reduction of muscle force by 60% during static stoop activity at the L5/S1 location. The study indicated that workers using exoskeletons for longer periods may experience a loss of functionality, as forward bending posture is an extremely constrained maneuver (Kazerooni et al, 2019;SuitX, 2019).…”
Section: Spring-actuated Devicesmentioning
confidence: 99%
“…Considering that almost 33% of all cases of occupational injuries and illness requiring days away from work are attributed to WMSDs wherein back disorder accounts for 43% of these cases (Kim et al, 2019, Umer et al, 2017, it is imperative to explore the suitability of emerging technologies such as BSEs for construction work. BackX exoskeleton is designed for use in different maneuvers such as squatting, cycling, walking, and climbing ladders (Kazerooni et al, 2019), which are in line with the range of maneuvers assumed by the construction workers. But there are scarce studies assessing the implications of BSEs (like BackX) for construction-related tasks (e.g., rebar, flooring, and finishing).…”
Section: Research Gapmentioning
confidence: 99%